Illuminating the Persistence and Departures of Previously Disadvantaged Students at an Engineering Faculty - Bladergroen, M. C. (South African Journal of Higher Education, 2021)
The low success rate of many students from previously disadvantaged groups endangers the face and fate of many tertiary institutions, hence an Engineering Faculty’s explorations into the causes of these students’ persistence at and departures from the Faculty. By using the theory of acculturation and agency the research group explored students’ opportunity of freedom towards self-actualisation. Three sample groups were used and the noteworthy findings of the persistence groups’ questionnaire and the focus group findings were explored. The data suggest that the previously disadvantaged students experience a general sense of isolation and physical segregation. The study reports that Faculty has to make concerted efforts to acknowledge and appreciate the somatic and intellectual skills of PDAS, and utilize these towards academic support if they plan on increasing the retention rates. If not the students from previously disadvantaged backgrounds are systemically coerced to spend valuable academic time circumventing unpleasant experiences, change Faculty or drop out of the system.